Single dose sublingual testosterone and oral sildenafil vs. a dual route/dual release fixed dose combination tablet: a pharmacokinetic comparison. (7th March 2016) - Bloemers, Jos; van Rooij, Kim; de Leede, Leo; Frijlink, Henderik W.; Koppeschaar, Hans P. F.; Olivier, Berend; Tuiten, Adriaan
Abstract : Aim: The aim was to compare the pharmacokinetic profiles of two formulations of a combination drug product containing 0.5 mg testosterone and 50 mg sildenafil for female sexual interest/arousal disorder. The prototype (formulation 1) consists of a testosterone solution for sublingual administration and a sildenafil tablet that is administered 2.5 h later. The dual route/dual release fixed dose combination tablet (formulation 2) employs a sublingual and an oral route for systemic uptake. This tablet has an inner core of sildenafil with a polymeric time delay coating and an outer polymeric coating containing testosterone. It was designed to increase dosing practicality and decrease potential temporal non‐adherence through circumventing the relatively complex temporal dosing scheme. Methods: Twelve healthy premenopausal subjects received both formulations randomly on separate days. Blood was sampled frequently to determine the pharmacokinetics of free testosterone, total testosterone, dihydrotestosterone, sildenafil and N‐desmethyl‐sildenafil. Results: Formulation 2 had a higher maximum concentration ( C max ) for testosterone, 8.06 ng ml –1 (95% confidence interval [CI] 6.84, 9.28) and higher area under the plasma concentration–time curve (AUC), 7.69 ng ml –1 h (95% CI 6.22, 9.16) than formulation 1, 5.66 ng ml –1 (95% CI 4.63, 6.69) and 5.12 ng ml –1 h (95% CI 4.51, 5.73), respectively. Formulation 2 had a lower C max for sildenafil, 173 ng ml –1 (95% CI 126, 220) and a lower AUC, 476 ng ml –1 h (95% CI 401, 551) than formulation 1, 268 ng ml –1 (95% CI 188, 348) and 577 ng ml –1 h (95% CI 462, 692), respectively. Formulation 2 released sildenafil after 2.75 h (95% CI 2.40, 3.10). Conclusions: The dual route/dual release fixed dose combination tablet fulfilled its design criteria and is considered suitable for further clinical testing. What is Already Known about this Subject: Female sexual interest/arousal disorder (FSIAD) is a significant problem impacting psychological well‐being, but the pharmacotherapeutic options for this problem are lacking. The combined, on‐demand, sublingual administration of low dose sublingual testosterone and oral administration of sildenafil is a novel pharmacotherapeutic option under development for FSIAD. In proof‐of‐concept trials, these compounds were successfully administered via different dosage forms (sublingual and oral) at different time points (separated by 2.5 h) because of their markedly different pharmacokinetic–pharmacodynamic profiles. For future larger scale studies and the clinical practice, this raises obvious adherence issues. What this Study Adds: A newly developed dual route/dual release fixed dose combination tablet containing testosterone and sildenafil mimics the pharmacokinetic profile of these components when they are administered as different dosage forms, 2.5 h apart. This combination tablet is a suitable final pharmaceutical drug product that will be used in future studies.